Hierarchical Porous Chitosan Sponges as Robust and Recyclable Adsorbents for Anionic Dye Adsorption. Issue 1 (December 2017) - Wang, Mei; Ma, Yifei; Sun, Yan; Hong, Sung; Lee, Stephanie; Yoon, Bumyong; Chen, Long; Ci, Lijie; Nam, Jae-Do; Chen, Xuyuan; Suhr, Jonghwan
Abstract Biomass waste treatment and detrimental dye adsorption are two of the crucial environmental issues nowadays. In this study, we investigate to simultaneously resolve the aforementioned issues by synthesizing chitosan sponges as adsorbents toward rose bengal (RB) dye adsorption. Through a temperature-controlled freeze-casting process, robust and recyclable chitosan sponges are fabricated with hierarchical porosities resulted from the control of concentrations of chitosan solutions. Tested as the adsorbents for RB, to the best of our knowledge, the as-prepared chitosan sponge in this work reports the highest adsorption capacity of RB (601.5 mg/g) ever. The adsorption mechanism, isotherm, kinetics, and thermodynamics are comprehensively studied by employing statistical analysis. Importantly and desirably, the sponge type of chitosan adsorbents exceedingly facilitates the retrieving and elution of chitosan sponges for recyclable uses. Therefore, the chitosan sponge adsorbent is demonstrated to possess dramatically squeezable capability with durability for 10, 000 cycles and recyclable adsorption for at least 10 cycles, which provides an efficient and economical way for both biomass treatment and water purification.